The Stakeholders’ Perception on the Reliability and Validity of Internal Assessment - Khanal, Rajendra (KMC Research Journal, 2021)
This article presents the stakeholders’ perceptions of the reliability and validity of the internal assessment system at Masters’ level under the faculty of Education, Tribhuvan University. It is based on mixed-method research design as well as primary and secondary data sources. For this purpose, the purposive sampling technique was applied to select 100 master’s level students studying in semester system and 25 teachers who were involved in teaching at the same level. The respondent views and perceptions have been analyzed and interpreted as descriptively and analytically. The findings depict that only 42 percent of students and 48 percent of teachers were agreed with the reliability of the score achieved from internal assessment. It can say that their level of satisfaction has signified as a weaker position. Likewise, 38 percent of students and 36 precent of teachers agreed on the tools used in internal evaluation, and their level of satisfaction is seen as very poor. However, they agreed that the tools used for internal assessment possess all sorts of validity. The findings conclude that internal assessment doesn’t have a higher level of reliability and validity.